Optimizing workover job types as one of company strategies to increase short-term investment returns under low oil price - Jermia, Jermia; Sukarno, Subiakto (The Indonesian Journal of Business Administration, 2018)
Abstract. The oil price has been low since 2004 and reached a 10-year low in 2016. Oil companies must adapt their strategy to keep their financial performance. Chevron corporation has re-focus its strategy, with one of the focuses is to improve free cash flow through improving its short-term investment returns. Best Company, one of its subsidiaries, faces a challenge on how to add more opportunities to align with this strategy. This paper reviews workover activities, as one of business activities besides capital projects in Best Company, to find opportunity for increasing its economic returns. The research is studying measures on workover activities that can be built into a quantitative predictive model to find best strategy for maximizing its efficiency or financial return. The quantitative predictive model also further allows optimization of the Company’s portfolio, as it allow direct comparison with capital projects within the portfolio.Based on the research, it is shown that the rig count has almost linear relationship with NPV under similar profitability index for various spending when the job type mix remains the same. However, when the job type mix is optimized, it is shown that the company can increase its returns by focusing on pump upsize and water shutoff job types. In the case of Best Company, an optimization in the job type mix at the same number of workover rigs can be expected to increase the profitability index (marginal benefit) from 1.42 to 1.53 for the investment in workover business. Keywords: Workover, Forecasting, Low oil price, Strategy, Optimization